-(-1)-4=

Simple and best practice solution for -(-1)-4= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(-1)-4= equation:


Simplifying
-1(-1) + -4 = 0

Multiply -1 * -1
1 + -4 = 0

Combine like terms: 1 + -4 = -3
-3 = 0

Solving
-3 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| X(y-2)=y+1 | | y=-0-4 | | 4-x=6-x | | 3.4x+7=5.7x+2 | | x(6-x)=-16 | | 9x=2-11x | | x=-5x+3 | | 16=-x+7 | | 6(2y-6)=4(9+3y) | | -2=-x+7 | | x-2/3=x | | 3x+4+2x=14 | | x^2+3x=-4 | | 2x+10x=x+2+3000 | | x=y+60 | | 0=-x+7 | | (5x-4)-(3x-1)=3 | | y=7+-1x | | 5(2y+3)=4 | | 1=.5x-4 | | y=.5(-6)-4 | | 13-2y=3 | | 3y+2(y+2)=13-(2y-5) | | 3x^2+10=1 | | x-2(-3)=3 | | x=3+2y | | 150-2x=34x+22 | | 4*a*a-2*a-4=0 | | 72+8x=-72 | | 3x+12=75-6 | | 3+2(x+1)-x=12 | | -23=-2-10+a |

Equations solver categories